Sleep spindles are resilient to extensive white matter deterioration. Issue 2 (13th June 2020) - Sanchez, Erlan; Arbour, Caroline; El-Khatib, Héjar; Marcotte, Karine; Blais, Hélène; Baril, Andrée-Ann; Bedetti, Christophe; Descoteaux, Maxime; Lina, Jean-Marc; Gilbert, Danielle; Carrier, Julie; Gosselin, Nadia
Abstract: Sleep spindles are an essential part of non-rapid eye movement sleep, notably involved in sleep consolidation, cognition, learning and memory. These oscillatory waves depend on an interaction loop between the thalamus and the cortex, which relies on a structural backbone of thalamo-cortical white matter tracts. It is still largely unknown if the brain can properly produce sleep spindles when it underwent extensive white matter deterioration in these tracts, and we hypothesized that it would affect sleep spindle generation and morphology. We tested this hypothesis with chronic moderate to severe traumatic brain injury ( n = 23; 30.5 ± 11.1 years old; 17 m/6f), a unique human model of extensive white matter deterioration, and a healthy control group ( n = 27; 30.3 ± 13.4 years old; 21m/6f). Sleep spindles were analysed on a full night of polysomnography over the frontal, central and parietal brain regions, and we measured their density, morphology and sigma-band power. White matter deterioration was quantified using diffusion-weighted MRI, with which we performed both whole-brain voxel-wise analysis (Tract-Based Spatial Statistics) and probabilistic tractography (with High Angular Resolution Diffusion Imaging) to target the thalamo-cortical tracts. Group differences were assessed for all variables and correlations were performed separately in each group, corrected for age and multiple comparisons. Surprisingly, although extensive white matter damage across the brain including all thalamo-cortical tracts was evident in the brain-injured group, sleep spindles remained completely undisrupted when compared to a healthy control group. In addition, almost all sleep spindle characteristics were not associated with the degree of white matter deterioration in the brain-injured group, except that more white matter deterioration correlated with lower spindle frequency over the frontal regions. This study highlights the resilience of sleep spindles to the deterioration of all white matter tracts critical to their existence, as they conserve normal density during non-rapid eye movement sleep with mostly unaltered morphology. We show that even with such a severe traumatic event, the brain has the ability to adapt or to withstand alterations in order to conserve normal sleep spindles. Abstract : Many essential functions of sleep rely on sleep spindles. We show here that even with extensive brain damage to critical networks, the brain has the capacity to adapt or to withstand alterations in order to conserve normal sleep spindles, which challenges current hypotheses and speaks to their importance and resilience. Graphical Abstract: